Survival of the African white‐backed vulture Gyps africanus in north‐eastern South Africa. (14th August 2012) - Monadjem, Ara; Botha, Andre; Murn, Campbell
Abstract Old World vultures are in decline across their entire range. Although critical for the formulation of effective conservation measures, neither survival nor movement patterns of African vultures are adequately known. This paper presents survival and movement data on the African white‐backed vultures (Gyps africanus) from South Africa. Survival estimates were modelled on resightings of tagged vultures. Birds were captured en masse and resighted between November 2005 and December 2010. A total of 93 adult and subadult birds were fitted with uniquely numbered patagial tags, which were resighted 3707 times(mean of 39.8 resightings per bird). The programme MARK was used to estimate survival. The best model was one where survival and recaptures varied only with time (e.g. year). However, owing to the fading (illegibility) of tags in later years, the relationship with time is probably spurious. The second best model was one where survival and recaptures varied with age and time. Annual survival estimates increased from 85.2% in second‐year birds to 99.9% in adults. This corresponds well with the survival of two other Gyps vultures that have been studied to date and underscores the point that additional mortality of adults in these long‐lived species will result in rapid population declines.